2020
DOI: 10.3390/molecules26010162
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus spp. Mycelia Enriched in Magnesium and Zinc Salts as a Potential Functional Food

Abstract: Worldwide, mushrooms belonging to the Pleurotus spp. such as P. citrinopileatus, P. djamor, and P. pulmonarius are highly valued not only for their taste and aroma but also for their health-promoting properties. These species are rich in bioelements, vitamins, and above all, compounds that exhibit immunostimulatory activity. Therefore, in this study, we aimed to determine the effect of the supplementation of culture media using inorganic Mg and Zn salts. This is the first study to establish the bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The concentration of Mg in the samples of P. ostreatus in the study by Zakil et al [ 32 ] ranged from 270 mg kg −1 to 1140 mg kg −1 . The research done by Włodarczyk et al [ 43 ] found that addition of inorganic Zn and Mg salts into the media resulted in the increase of the production biomass by 30% and in the increase of bioaccumulation of the inorganic salts.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of Mg in the samples of P. ostreatus in the study by Zakil et al [ 32 ] ranged from 270 mg kg −1 to 1140 mg kg −1 . The research done by Włodarczyk et al [ 43 ] found that addition of inorganic Zn and Mg salts into the media resulted in the increase of the production biomass by 30% and in the increase of bioaccumulation of the inorganic salts.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical analysis was performed with the HPLC-DAD method, as described previously [ 12 , 46 ]. Methanolic extracts obtained in the process were used for these estimations.…”
Section: Methodsmentioning
confidence: 99%
“…These values corresponded to 4284.89 and 3080.04 mg GAE/kg DM for PC and PD, respectively. In previous articles, the TPC of related mushrooms notably varied, and 14.14 mg GAE/150 g uncooked weight, [26] 297 mg GAE/100 g DM [27] and 2.03 mg GAE/g DM [28] values were reported for PC. On the other hand, 161 mg GAE/100 g DM, [27] and for maceration, 7.26–11.02 mg GAE/g DM and for Soxhlet extraction, 6.64–9.28 mg GAE/g DM [29] phenolic levels of PD were stated by several authors.…”
Section: Resultsmentioning
confidence: 99%